Evaluation of Information Technology Governance Related to Digital Transformation on The Alignment of Company Business Strategy Using Cobit 2019 And Fuzzy C-Means ( Case Study: Perumda Tirtanadi, North Sumatra Province) - Rahmat Rezki; Rian Farta Wijaya; Muhammad Syahputra Novelan (Utan Kayu Publishing, 2025)
Digital transformation has become a strategic necessity for public sector companies to improve efficiency and service quality. Perumda Tirtanadi of North Sumatra Province has implemented a meter reading system as part of its digital transformation initiative to improve the accuracy of water consumption data. The success of this system is strongly influenced by the effectiveness of Information Technology (IT) governance and its alignment with the company's business strategy. This research aims to evaluate IT governance of the meter reading system using the COBIT 2019 framework and the Fuzzy C-Means method. The evaluation was conducted through design factor analysis, assessment of process capability levels, capability gap analysis, and clustering of user satisfaction levels. The results indicate that the relevant objectives include EDM01, EDM03, APO12, APO13, DSS05, and MEA03, with capability levels at level 2 and level 3. The capability gap analysis reveals gaps of two to three levels, particularly in strategic domains. The Fuzzy C-Means clustering results show that most users belong to the “satisfied” cluster, indicating that the system adequately supports operational needs despite existing capability gaps. This study provides recommendations and a governance improvement roadmap to support digital transformation and business strategy alignment